Exploring segmented assimilation theory in health education utilization and its influencing factors among internal migrants in China: insights from the 2017 China migrants dynamic survey - Xu, Ting; Wang, Zeyu; Wang, Tingting; Shi, Jiahua; Zhu, Aiyong; Dong, Enhong (Frontiers in Public Health, 2025)
IntroductionThis study investigated segmented assimilation patterns and factors influencing health education utilization (HEU) among internal migrant populations in China, driven by concerns over their declining health owing to urbanization-related changes.MethodsData from the 2017 China Migrants Dynamic Survey were analyzed, focusing on 13,998 rural migrants. Negative binomial regression was used to explore assimilation patterns and determine the factors affecting HEU among internal migrants in China.ResultsThe results revealed diverse assimilation patterns among internal migrants in four clusters: first-generation classic assimilation, first-generation integration assimilation, second-generation segmented assimilation, and second-generation underclass assimilation. Adjusting for socioeconomic factors, first-generation integrated assimilation groups showed lower HEU (IRR = 0.922, p < 0.01), while second-generation underclass groups demonstrated higher HEU (IRR = 1.110, p < 0.001) than the second-generation segmented assimilation groups. Additionally, factors such as ethnicity, marital status, employment status, educational attainment, hukou type, health insurance type, time of access to healthcare, social integration, social participation, establishment of health records, and issues encountered in host and origin places significantly influenced HEU.DiscussionThis study highlights diverse assimilation patterns among Chinese internal migrants regarding HEU, consistent with the theory of segmented assimilation. Specifically, second-generation immigrants exhibit higher HEU levels than their first-generation counterparts, with the second-generation underclass demonstrating the highest HEU. These findings underscore the need for targeted policy interventions addressing diverse migrant assimilation patterns. Specifically, first-generation migrants require accessible and culturally adapted health education programs to overcome systemic barriers, while second-generation underclass migrants need sustained support to leverage their engagement in health initiatives.